Dreams - Schreiner, Olive, 1855-1920 (Salt Lake City, UT : Project Gutenberg, 1998)
"Dreams" by Olive Schreiner is a collection of eleven short stories published in 1890. Set in the African landscape, these allegorical tales explore profound themes through dream sequences. The collection's most notable story follows a woman's journey through three fragmented dreams, depicting the struggles between Man and Woman, the quest for Freedom guided by figures like Truth and Reason, and visions of a harmonious future. Through symbolic characters and metaphorical crossings, Schreiner examines gender expectations, male dominance, and the difficult path toward equality and freedom. (This is an automatically generated summary.)
The lost joy -- The hunter -- The gardens of pleasure -- In a far-off world -- Three dreams in a desert -- A dream of wild bees -- In a ruined chapel -- Life's gifts -- The artist's secrets -- I thought I stood -- The sunlight lay across my bed
Wikipedia page about this book: https://en.wikipedia.org/wiki/Three_Dreams_in_a_Desert
Release date is 1998-08-01
Produced by Sue Asscher, and David Widger
Keywords: Dreams; Women -- Fiction